Analysis of BUMDes Circular Economy-based Business Unit Development (Case Study in Sanankerto Village, Malang Regency) - Lestari, Wiji Indah; Wahjoedi, Wahjoedi; Dwiputri, Inayati Nuraini (Journal of Applied Business, Taxation and Economics Research, 2024)
BUMDes Kerto Raharjo has several business units including ecotourism, a grocery store, and a bioconversion house for organic waste with maggot cultivation or based on a circular economy. To the best of the researcher's knowledge, empirical studies on the topic of circular business are still lacking, particularly at the BUMDes business unit level which significantly analyses the development of business units. Therefore, this study aims to analyze the development of BUMDes circular economy-based business units as well as the supporting and inhibiting factors faced. This research uses a qualitative approach with a case study design. Afterward, the cases were analyzed by adopting the Miles & Huberman interactive model. The results showed that business unit development was conducted with different products or services (diversification). Supporting factors in business unit development include organizational commitment to sustainability, technology, university involvement, as well as the involvement of the Regional Research and Development Agency. Meanwhile, inhibiting factors in the development of business units include the lack of raw materials, limited financial support independently, low community involvement in sorting, low involvement of supply partners, and the absence of regulatory/mechanism innovations. This research seeks to contribute to existing knowledge and is a stepping stone for the refinement and stabilization of business unit development.